Transcriptome and Physiological Analysis Reveals the Mechanism of Abscisic Acid in Regulating Cadmium Uptake and Accumulation in the Hyperaccumulator Phytolacca acinosa Roxb. - Qin Xie; Wenting Xu; Qing Wang; Feihong Yao; Yachao Jiang; Haijia Cao; Wanhuang Lin (Plants)
Cadmium (Cd) is an extremely toxic heavy metal that can move from the soil to plants and enter the human body via the food chain, causing severe health issues for humans. Phytoremediation uses hyperaccumulators to extract heavy metals from polluted soil. Phytohormones, wildly used plant growth regulators, have been explored to improve phytoremediation efficiency. Abscisic acid (ABA) is also an essential regulator of plant tolerance to biotic and abiotic stresses, including heavy metal-induced toxicity. Previous research has revealed that Phytolacca acinosa Roxb. (P. acinosa) has a strong ability to enrich Cd and can be used as a Cd hyperaccumulator. In this study, physiological and biochemical analysis revealed that under Cd stress, exogenous ABA application alleviated oxidative stress, increased the Cd2+ concentration in P. acinosa, especially in the roots, and changed the phytohormone concentration in P. acinosa. Transcriptome analysis was conducted to explore the molecular mechanisms by which ABA regulates Cd uptake and accumulation in P. acinosa, and to further understand the regulatory role of ABA. The results show that ABA treatment affected gene expression in P. acinosa roots under Cd stress. This study identified 5788 differentially expressed genes (DEGs) (2541 up-regulated and 3247 down-regulated). Moreover, 96 metal transport-related DEGs, 54 phytohormone-related DEGs, 89 cell wall-related DEGs, 113 metal chelation-related DEGs, and 102 defense system-related DEGs cooperated more closely under exogenous ABA application to regulate Cd uptake and accumulation in P. acinosa under Cd stress. These results may help to elucidate the mechanisms by which ABA regulates Cd uptake and accumulation in plants, and provide a reference for developing a phytohormone-based strengthening strategy to improve the phytoremediation ability of other hyperaccumulators or accumulator species. The key genes involved in ABA’s regulation of Cd uptake and accumulation in P. acinosa need to be further analyzed and functionally verified. This may expand our understanding of the molecular regulatory mechanisms underlying heavy metal uptake and accumulation in hyperaccumulators.